Pelatihan Pembelajaran Membaca Alquran Dan Kenal Huruf Alquran Bagi Para Driver Ojek Online Ghost Riders Family Medan - G Gunawan (Jurnal Penelitian Medan Agama, 2019)
This paper illustrates the real conditions of the Ojol drivers who are working on the streets, who are not worried about themselves, not even a few of them (who are Muslim) who have begun to forget the reading of the Qur'an and don't even understand it at all. We know that in the verse of Al-Qur'an on the letter Al-Muddatsir has been ordered by Allah SWT. that in reading the Qur'an it is sought to read it in a tartil. It gives a clue that we as Muslims who have Al-Qur'an guidelines must be able to read it properly and correctly. In harmony with the first revelation received by the Prophet Muhammad. in the cave of Hera 'is the letter Al-Alaq, paragraph (1) up to verse (5) which in the verses contains instructions to read. There is written "Iqra '" which means "reading". Based on the verses mentioned above, it is a suggestion for all the people of the Prophet Muhammad to always read and study. So with that suggestion it is very inappropriate for Muslims to remain in such conditions, because Muslims have guidelines, namely the Qur'an and Al-Hadith. Based on this, it is hoped that the existence of similar training and guidance for Ojol drivers in always reminding them of the holy book of the Koran, and slowly learning to understand the contents of the guidelines can also read Arabic writing.